Anti-corruption agencies: between empowerment and irrelevance - De Sousa, Luís (Crime, law and social change, 2010)
The anti-corruption activity of the 1990s is characterized by the rise of new players, such as specialized anti-corruption bodies. Anti-corruption agencies (ACAs) are public bodies of a durable nature, with a specific mission to fight corruption and reducing the opportunity structures propitious for its occurrence in society through preventive and/or repressive measures. Independently of their format and powers, ACAs encounter various constraints to their mandate, which explains the meagre results obtained by some of them. This introductory paper tries to understand the rise, future, and implications of this new kind of "integrity warrior" and to locate them in the evolving doctrine of corruption control. The objective of this edited volume is to re-launch the debate on ACAs as the most innovative feature of the anti-corruption movement of the last two decades.